Представители рода Syphacia Sеurat, 1916 (Nematode, Syphaciidae) в фауне УССР - Шарпило, Л.Д. (Вестник зоологии, 1973)
In rodents of the families Muridae and Cricetidae from the fauna of the Ukraine 9 species of the genus Syphacia Seurat, 1916 are found, 6 of which are first registered in the territory of the republic, 4 — in the USSR fauna and 2 — are new for science. The
identification key, drawings of all the found species and brief information on them, descriptions and differentiative diagnose's of the new species are given.